Numerical experimentation on focusing time and neutron yield in GN1 plasma focus machine - Arwinder, Singh*; Lee, S.; Saw, S. H. (World Scientific Publishing Co Pte Ltd, 2014)
In this paper, we have shown how we have fitted Lee’s six phase model code to analyze the current waveform of the GN1 plasma focus machine working in deuterium gas. The Lee’s 6-phase model codes was later configured to work between 0.5 to 6 Torr and the results of both focusing time and neutron yield was than compared with the published experimental results. The final results indicate that Lee’s code, gives realistic plasma dynamics and focus properties together with a realistic neutron yield for GN1 plasma focus, without the need of any adjustable parameters, needing only to fit the computed current trace to a measured current trace.